1991
DOI: 10.1007/bf00201502
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of photosystems I and II in pea leaves exposed to heat stress in the presence or absence of light

Abstract: Fluorimetric, photoacoustic, polarographic and absorbance techniques were used to measure in situ various functional aspects of the photochemical apparatus of photosynthesis in intact pea leaves (Pisum sativum L.) after short exposures to a high temperature of 40 ° C. The results indicated (i) that the in-vivo responses of the two photosystems to high-temperature pretreatments were markedly different and in some respects opposite, with photosystem (PS) II activity being inhibited (or down-regulated) and PSI fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
1
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(122 citation statements)
references
References 38 publications
9
111
1
1
Order By: Relevance
“…As found in pea leaves (Havaux et al 1991), light protected photochemical activity against inactivation by heat. This photoprotection was saturated at low PFD (65 jjivaoi vcT s~').…”
Section: Thermal Tolerance Pfd and Water Regimesupporting
confidence: 53%
“…As found in pea leaves (Havaux et al 1991), light protected photochemical activity against inactivation by heat. This photoprotection was saturated at low PFD (65 jjivaoi vcT s~').…”
Section: Thermal Tolerance Pfd and Water Regimesupporting
confidence: 53%
“…Within the photosynthetic apparatus, PSII seems to be the most heat-sensitive function, whereas PSI activity, stromal enzymes, or chloroplast envelope are comparatively much more thermostable (3,5,12,18,29). It is believed that increasing temperature leads first to a blockage of PSII reaction centers and then to a dissociation of antennae pigmentprotein complexes from the central core of the PSII lightharvesting apparatus (2,3,10).…”
Section: Methodsmentioning
confidence: 99%
“…The photoacoustic signals generated by small leaf discs (diameter, 1 cm) at 250C were measured with a custom-made photoacoustic spectrometer that has been described (12) …”
Section: Photoacoustic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…E¡ect of heat stress on the rate of re-reduction of P700 + after far-red illumination in the ndh mutant v1 Previous work has shown that mild heat stress of pea [7] and potato [8] leaves induces a dramatic increase in the rate of re-reduction of P700 in the dark after a period of far-red illumination. This type of assay gives a measure of the rate of PSII-independent reduction of PSI and is comprised of both cyclic electron transfer around PSI and electron donation to the intersystem electron transfer chain by stromal reductant [8,12].…”
Section: 1mentioning
confidence: 99%